The relationships between job embeddedness, work-family conflict, and the impact of gender on turnover intention : evidence from the Indonesian banking industry - Kismono, Gugup (Curtin University, 2011)
This research examined the relationships between job embeddedness, work-family conflict and turnover intention. It also examined the impact of gender on the relationships between these variables. While previous studies had been undertaken to date regarding organisations in Western (individualistic) countries, the relationships between these variables had not been empirically tested using samples from Eastern (collectivistic) cultures.A quantitative research design and methodology were adopted for the research. Data was drawn from a sample of 1,122 employees in the Indonesian banking industry, through a questionnaire survey measuring job embeddedness, work-family conflict and turnover intention. The sample consisted of 606 male and 516 female respondents.An evaluation of items measuring job embeddedness using formative model procedures produced 16 valid items; 10 items measuring on-the-job embeddedness and 6 items measuring off-the-job embeddedness. The items measuring workfamily conflict and turnover intention were confirmed to have adequate validity and reliability.A Structural Equation Modelling (SEM) approach with Amos 7 (Arbuckle 2006) was used to test the hypothesised relationships between job embeddedness, workfamily conflict and the impact of gender on turnover intention. Analyses found that on-the-job embeddedness negatively correlated with turnover intention, and the relationship between off-the-job embeddedness and turnover intention was insignificant. A significant negative correlation was found between work interfering with family (WIF) and turnover intention, in addition to a significant positive correlation between family interfering with work (FIW) and turnover intention. It was also found that gender has no impact on the relationships between the variables studied. The results support the importance of on-the-job embeddedness, the need to support employees in carrying out their family and community activities, and the lack of difference between genders in seeking work-life balance.The implications for business practices in light of the relationships between job embeddedness, work-family conflict and the impact of gender on turnover intention were considered in this research. Organisations need to develop employees' levels of on-the-job embeddedness, as well as job involvement, given that on-the-job embeddedness negatively, and WIF positively, correlated with turnover intention. The application of flexible working hours and provision of flexibility in taking maternity (or parental) leave should also be encouraged. These policies are beneficial for both male and female employees as it was found that gender had no moderating impact on the relationships between the variables.